Research on different techniques in breast cancer radiotherapy - Dogan, Mehmet Hakan; Burhanedtin Zincircioglu, Seyit; Aydinol, Mahmut (Contemporary Oncology/Współczesna Onkologia, 2013)
In breast cancer radiotherapy, the internal mammary lymphatic chain is treated in the target volume in a group of patients with high risk criteria. There are a number of different techniques in breast radiotherapy because of the variability of the anatomic region, structures and risk criteria in the irradiation field. When irradiating the target volume we also consider homogeneity of dose distribution and minimizing the dose to critical structures such as the heart and lung. In this study, we have evaluated the dose distribution of different radiotherapy techniques in twelve patients with left breast cancer who had breast conserving surgery or mastectomy. A two-dimensional computerized planning system (2-DCPS) was used for each patient to compare wide-field, oblique photon-electron, perpendicular photon-electron and oblique-electron techniques in terms of dose homogeneities in the target volume, the doses received by the heart and lung, and the coverage of the internal mammary chain. Critical structures were irradiated with acceptable dose percentages besides the internal mammary chain with both wide-field, photon-electron and oblique-electron techniques. The wide-field technique was easy to perform and exposed the heart to a smaller radiation dose than photon-electron techniques. The oblique electron techniques provide a minimal radiation dose to critical structures. In oblique electron techniques, if the internal mammary chain was not covered in the target volume, the heart dose was minimized. In conclusion, we suggest using oblique-electron techniques in breast irradiation where the internal mammary is in the target volume.